NP body domain and PB2 contribute to increased virulence of H5N1 highly pathogenic avian influenza viruses in chickens - Tada, Tatsuya; Suzuki, Koutaro; Sakurai, Yu; Kubo, Masanori; Okada, Hironao; Itoh, Toshihiro; Tsukamoto, Kenji (Journal of virology, 2011)
The molecular basis of pathogenicity of H5N1 highly pathogenic avian influenza (HPAI) viruses in chickens remains largely unknown. H5N1 A/chicken/Yamaguchi/7/2004 virus (CkYM7) replicates rapidly in macrophages and vascular endothelial cells in chickens, causing sudden death without fever or gross lesions, while H5N1 A/duck/Yokohama/aq10/2003 virus (DkYK10) induces high fever, severe gross lesions, and a prolonged time to death, despite the 98% amino acid identity between the two viruses. To explore the molecular basis of this difference in pathogenicity, a series of eight single-gene reassortant viruses from these HPAI viruses were compared for pathogenicity in chickens. Two reassortants possessing the NP or PB2 gene from DkYK10 in the CkYM7 background reduced pathogenicity compared to other reassortants or CkYM7. Inversely, reassortants possessing the NP or PB2 gene of CkYM7 in the DkYK10 background (rgDkYK-PB2(Ck), rgDkYK-NP(Ck)) replicated quickly and reached higher titers than DkYK10, accompanied by more rapid and frequent apoptosis of macrophages. The rgDkYK-NP(Ck) and rgDkYK-PB2(Ck) reassortants also replicated more rapidly in chicken embryo fibroblasts (CEFs) than did rgDkYK10, but replication of these viruses was similar to that of CkYM7 and DkYK10 in duck embryo fibroblasts. A comparison of pathogenicities of seven rgDkYK10 mutants with a single amino acid substitution in NP(Dk) demonstrated that valine at position 105 in the NP(Ck) was responsible for the increased pathogenicity in chickens. NP(Ck), NP(105V), and PB2(Ck) enhanced the polymerase activity of DkYK10 in CEFs. These results indicate that both NP and PB2 contribute to the high pathogenicity of the H5N1 HPAI viruses in chickens, and valine at position 105 of NP may be one of the determinants for adaptation of avian influenza viruses from ducks to chickens.